Strong impact of ethnicity on effectiveness of the first trimester maternal serum screen of fetal Down syndrome. (2nd November 2018) - Lerthiranwong, Thitikarn; Wanapirak, Chanane; Sirichotiyakul, Supatra; Tongprasert, Fuanglada; Srisupundit, Kasemsri; Luewan, Suchaya; Tongsong, Theera
Abstract: Objectives: The objective of this study is to compare the effectiveness of first-trimester maternal serum screening (MSS) for fetal Down syndrome among Thai women between the method using Caucasian reference ranges with racial factor correction (CRR-RC) and that using Thai reference ranges (TRR). Methods: A prospective database of MSS was accessed. The levels of PAPP-A and beta-hCG were calculated to determine their MoMs (multiple of medians) by two methods: (1) CRR-RC for Asian women and (2) TRR. The MoMs from both methods were used to determine the fetal risk. Results: Of 24, 885 women including 36 fetuses with Down syndrome, the detection rates were significantly higher with TRR when compared with CRR-RC, 77.8 and 63.9%, respectively, p  < .001. Additionally, the false-positive rates were significantly lower with TRR when compared to CRR-RC (7.5 versus 12.5%, respectively, p  < .001) Conclusions: The effectiveness of MSS was much better by using our own reference ranges rather than the method of racial factor correction. The important insight is that ethnicity strongly impacts on the effectiveness that cannot be completely corrected by ethnic factor. MSS derived by the CRR-RC in other regions should be interpreted with high precaution, especially where the biophysical characteristics of the women are much different from Caucasian population.